Teacher Competence Based on Digital Quotient as Instructional Leadership - Syunu Trihantoyo; Nuri Herachwati; Rudi Purwono (Faculty of Education Universitas Negeri Malang, 2021)
Abstract: The purpose of the study was to determine the digital intelligence-based teacher competence in carrying out the role as an instructional leadership. Digital intelligence-based teacher competence is related to the teacher’s ability to prepare the learning process, especially learning with virtual models during the COVID-19 pandemic. This research uses a qualitative approach with case studies. This research case relates to the digital intelligence-based teacher competence at SD Al-Azhar 35 Surabaya. The research was carried out in 2021, the object of research was carrying out virtual learning. Data were taken by interview, observation, and documentation study. Data analysis was carried out through the stages of data condensation, displaying, as well as drawing conclusions and verification. The results of the study showed that the digital intelligence-based teacher competence at SD Al-Azhar 35 Surabaya was initially motivated by the formulation of a vision that became an institution of direction and work instructions for all civitas, namely “developing the Qur’an generation through digital literacy”. The digital intelligence-based teacher competence is illustrated by three learning activities, namely the teaching and learning process, digital learning media management, and continuous self-development through a digital management system. The three activities describe teacher learning leadership in managing classrooms in maximizing teacher competence for optimal student learning outcomes.